Ishige okamurae and diphloroethohydoxycarmalol inhibit palmitic acid-impaired skeletal myogenesis and improve muscle regenerative potential. (December 2021) - Jayawardena, Thilina U.; Nagahawatta, D.P.; Lu, Yu-An; Yang, Hye-Won; Je, Jun-Geon; Kim, Seo-Young; Jeon, You-Jin
Graphical abstract: Highlights: Mechanistic insights into palmitic acid (PA)-impaired skeletal myogenesis. PA repress myogenic factors and enhances of adipogenic factor expression. IO and purified diphloroethohydoxycarmalol (DPHC) improve regenerative capacity. IO and DPHC as a nutritional intervention for PA-impaired skeletal myogenesis. Abstract: Obese sarcopenia is associated with palmitic acid (PA), an abundant circulating saturated fatty acid. This study examined a non-cytotoxic concentration of PA to provide mechanistic insights into PA-impaired skeletal myogenesis and potential medicinal and dietary interventions through edible brown seaweed, Ishige okamurae (IO). C2C12 cells were examined for myogenic markers, adipogenic factors, and regenerative capacity through growth regulators against PA interference to assess IO and purified diphloroethohydoxycarmalol (DPHC) as potential treatments. Both IO and DPHC improved myogenic marker (myogenin, MyoD, and MyHC) levels. PA down-regulated myogenic markers while improving adipogenic factors (PPARγ, c/EBPα, A-FABP), DPHC significantly arbitrated the negative effects. DPHC treatment also improved phosphorylation of the growth regulatory PI3K/Akt/mTOR axis over the adverse effects of PA. The results of this study suggested regulatory mechanisms through which the bioactive components IO and DPHC based on the sustainable utilization of I. okamurae inhibited the PA-induced impairment of skeletal myogenesis.